Preliminary validity evidence for a rapid fundamental movement skill assessment tool for primary education settings - Simpson, Aaron; Ward, Brodie; Rosenberg, Michael; Jackson, Ben; Gou, Jingdan; Derbyshire, Amanda; Thornton, Ashleigh L. (Frontiers in Sports and Active Living, 2025)
IntroductionAssessment of motor competence is critical for planning and monitoring children's development. However, many assessment tools require time, training, and resources not available to most teachers. We aimed to evaluate the external aspect of construct validity of a rapid product-oriented fundamental movement skill assessment tool designed specifically for primary education settings.MethodsFundamental movement skills of 73 children aged 4–8 were assessed using the KIDDO Challenge assessment tool and the Test of Gross Motor Development-2 (TGMD-2). We conducted correlational analyses between scores derived from the assessment tools.ResultsWe found significant associations (ranging from weak to moderate in nature; r range = −0.17 to 0.68) between scores of individual skills on the KIDDO Challenge and the TGMD-2. Age- and gender-standardised overall proficiency ratings between assessment tools exhibited a significant moderate, positive correlation (r = 0.52, p < .01).ConclusionsOur findings indicate that the KIDDO Challenge and TGMD-2 were significantly associated in their assessment of children's overall fundamental movement skill proficiency. These findings may assist teachers or school administration in selecting rapid fundamental movement skill assessment tools with evidence of validity for motor competence screening in primary education settings.